2012
DOI: 10.1002/glia.22412
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes as a regulated source of retinoic acid for the brain

Abstract: Retinaldehyde dehydrogenases (RALDH) catalyze the synthesis of the regulatory factor retinoic acid (RA). Cultured astrocytes express several of the RALDH enzyme family, and it has been assumed that this can be extrapolated to astrocytes in vivo. However, this study finds that few astrocytes in the rodent brain express detectable RALDH enzymes, and only when these cells are grown in culture are these enzymes upregulated. Factors controlling the expression of the RALDHs in cultured astrocytes were explored to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…To screen for impaired RA synthesis in tumors, we first compared the transcript levels of retinol‐synthesizing enzymes (RDH10, RDH16, dehydrogenase/reductase member 9 [DHRS9], ALDH1A1, ALDH1A2, and ALDH1A3) in glioblastoma tissues ( n = 26) and normal brain biopsies ( n = 8) (Napoli, ; Shearer et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To screen for impaired RA synthesis in tumors, we first compared the transcript levels of retinol‐synthesizing enzymes (RDH10, RDH16, dehydrogenase/reductase member 9 [DHRS9], ALDH1A1, ALDH1A2, and ALDH1A3) in glioblastoma tissues ( n = 26) and normal brain biopsies ( n = 8) (Napoli, ; Shearer et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…To screen for impaired RA synthesis in tumors, we first compared the transcript levels of retinol-synthesizing enzymes (RDH10, RDH16, dehydrogenase/reductase member 9 [DHRS9], ALDH1A1, ALDH1A2, and ALDH1A3) in glioblastoma tissues (n 5 26) and normal brain biopsies (n 5 8) (Napoli, 2012;Shearer et al, 2012). Consistent with our hypothesis of impaired RA synthesis in glioblastoma, the expression of ALDH1A1, ALDH1A2, ALDH1A3, and DHRS9 was distinctly downregulated in tumors as compared with nontumorous brain tissue ( Fig.…”
Section: Downregulation Of Transcripts Associated With Ra Synthesis Imentioning
confidence: 99%
“…Moreover, we previously showed that RA treatment increases hippocampal expression of RARβ in middle‐aged rats, whereas RARα is decreased . Interestingly, it has been shown that, under conditions of low vitamin A, a local increase of RA could be detected in astrocytes to maintain a source of RA in the brain, suggesting that some RA receptors could be up‐regulated in VAD conditions …”
Section: Discussionmentioning
confidence: 96%
“…Such a scenario, where functional cells require exogenous RA produced by accessory cells for their survival and development appears to be a common theme among a variety of physiological systems. For example, gonadal germ cell fate is dictated by RA produced by mesonephroi (Bowles et al, 2006) whereas astrocytes provide a regulated source of RA for the brain (Shearer et al, 2012). RA is also provided to peripheral T lymphocytes by dendritic cells and this has been shown to imprint gut-homing specificity by enhancing the expression of integrin alpha4beta7 and chemokine receptor CCR9, an effect suppressed by the ALDH1A inhibitor citral (Iwata et al, 2004).…”
Section: Discussionmentioning
confidence: 99%